IDENTIFIKASI FAKTOR PENYEBAB VARIATION ORDER TERHADAP BIAYA DAN WAKTU PADA PROYEK LAVAYA NUSA DUA-BALI - IDA BAGUS GEDE INDRAMANIK; PUTU DODDY HEKA ARDANA; I PUTU GDE DHARMA PRAMANA (Universitas Mahasaraswati K. Mataram, 2024)
A construction project is a combination of cost, tools, and labor resources where in the process, the project owner works closely with contractors and suppliers to ensure that the project is of the right quality, time, and cost. In the process of implementing a construction project, of course, various problems will be found. One of the problems is Variation Order or less work. This study aims to find the factors that cause itVariation Order and impact Variation Order on project implementation both in terms of cost and implementation time in the Lavaya Nusa Dua-Bali Apartment project. The method used in this research is descriptive quantitative, where the data used in this research is only secondary data. Based on the results of this study it can be seen that 87.5% of all VO that occurs is dominated by construction factors caused by party requests owner. In addition, the impact of VO work also affects costs and time, where the impact of VO on costs causes an additional cost of 1,194% from the initial contract value of IDR 108,569,930,859.70 to IDR 109,866,110,410.02. Furthermore, for the impact on time, which has no impact on the overall project completion time target but has a direct impact on the contractor for the duration of work handover which has been delayed for 38 working days, from the initial duration of 99 working days to 62 working days.